Fonds or collection? a continuous debate in Archival Science - Fukuhara, Rodrigo [UNESP]; Troitino, Sonia [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2023)
The aim is to discuss the dualism between the concepts of fonds and collection, almost always conceived, respectively, as an organic and artificial assemblage of documents. The discussion inevitably refers to the Principle of Respect des Fonds and/or the Principle of Provenance, depending on the understanding of each author. Through a qualitative approach, the study reviews the archival literature in search of definitions and nuances for the two types of aggregation. Traditional categorization is often found to be problematic, generating doubts about the essential elements that determine the nature of the aggregation of records. Based on Geoffrey Yeo's reflections, an alternative view of the fonds-collection dualism is presented. The concepts of conceptual fonds and physical collection, proposed by Yeo, allow a continuum approach and open perspectives for the treatment of dispersed or mixed fonds, records with multiple provenances and body of records of questionable organic relationship.
Keywords: collection; fonds; principle of respect des fonds; principle of provenance